A comprehensive approach to identifying repurposed drugs to treat SCN8A epilepsy. (25th March 2018) - Atkin, Talia A.; Maher, Chani M.; Gerlach, Aaron C.; Gay, Bryant C.; Antonio, Brett M.; Santos, Sonia C.; Padilla, Karen M.; Rader, JulieAnn; Krafte, Douglas S.; Fox, Matthew A.; Stewart, Gregory R.; Petrovski, Slavé; et al.
Summary: Objective: Many previous studies of drug repurposing have relied on literature review followed by evaluation of a limited number of candidate compounds. Here, we demonstrate the feasibility of a more comprehensive approach using high‐throughput screening to identify inhibitors of a gain‐of‐function mutation in the SCN8A gene associated with severe pediatric epilepsy. Methods: We developed cellular models expressing wild‐type or an R1872Q mutation in the Nav 1.6 sodium channel encoded by SCN8A . Voltage clamp experiments in HEK‐293 cells expressing the SCN8A R1872Q mutation demonstrated a leftward shift in sodium channel activation as well as delayed inactivation; both changes are consistent with a gain‐of‐function mutation. We next developed a fluorescence‐based, sodium flux assay and used it to assess an extensive library of approved drugs, including a panel of antiepileptic drugs, for inhibitory activity in the mutated cell line. Lead candidates were evaluated in follow‐on studies to generate concentration‐response curves for inhibiting sodium influx. Select compounds of clinical interest were evaluated by electrophysiology to further characterize drug effects on wild‐type and mutant sodium channel functions. Results: The screen identified 90 drugs that significantly inhibited sodium influx in the R1872Q cell line. Four drugs of potential clinical interest—amitriptyline, carvedilol, nilvadipine, and carbamazepine—were further investigated and demonstrated concentration‐dependent inhibition of sodium channel currents. Significance: A comprehensive drug repurposing screen identified potential new candidates for the treatment of epilepsy caused by the R1872Q mutation in the SCN8A gene.